Augmentation Phalloplasty With Autologous Dermal Fat Graft in the Treatment of "Small Penis". (February 2016) - Xu, Lisi; Zhao, Muxin; Chen, Wen; Li, Yangqun; Yang, Zhe; Ma, Ning; Wang, Weixin; Feng, Jun; Liu, Qiyu; Ma, Tong
Abstract : Background: Our objective is to report on the efficacy and safety of dermal fat graft in augmentation phalloplasty performed on patients who presented complaining of "small penis, " and evaluate the cosmetic and psychological outcomes of it. Methods: From April 2010 and January 2015, 23 Chinese adult patients aged 18 to 33 years (average, 23 years) with subjective perception of small penis were included; all who requested an increase in the penile dimension underwent penile elongation (suprapubic skin advancement—ligamentolysis) and girth enhancement by dermal fat graft. Besides objective measurement, Male Genital Image Scale was used to facilitate selection of patients and evaluate the outcome, respectively. The change and shrinkage of the dermal fat strips was evaluated by ultrasound examination and computed tomography. Results: No major complications or erection deficiencies occurred during the postoperative follow-up period. After 6 months, the mean flaccid length was increased by 2.27 ± 0.54 cm, whereas the mean flaccid circumference gain was 1.67 ± 0.46 cm. Significant improvement of genital satisfaction was reported during the follow-up. The shrinkage of dermal fat strips was inconspicuous, and no curvature was observed due to fibrosis. Conclusions: With strict patient selection, this procedure is proved to be a plausible and reasonable option for patients with penile dysmorphophobia. Also, it provides a potential alternative procedure to current dominant methods and promotes the aesthetic results with penile lengthening.